The home buyer's : - McLean, Andrew James (Wiley, 2004)
The Home Buyer’s Advisor shows you precisely what to look for in a real estate investment, where to find the best buying opportunities, how to use proven holding strategies such as land-banking and lease options, and how to make your home a secure foundation for future real estate investments. Ideas for a secure retirement are also included. Packed with ideas, strategies, and real-world examples, Andrew McLean’s Home Buyer’s Advisor will show you how to Take advantage of a wide range of financing methods, such as originating new VA, FHA, and conventional loans; loan assumption; wrap-around loans; and other alternative financing methods.